Stakeholder perspectives on the use of pig meat inspection as a health and welfare diagnostic tool in the Republic of Ireland and Northern Ireland; a SWOT analysis. Issue 1 (December 2016) - Devitt, C.; Boyle, L.; Teixeira, D.; O'Connell, N.; Hawe, M.; Hanlon, A.
Abstract Background A SWOT (Strengths, Weaknesses, Opportunities and Threats) analysis is a strategic management tool applied to policy planning and decision-making. This short report presents the results of a SWOT analysis, carried out withn  = 16 stakeholders i) involved in the pig industry in the Republic of Ireland and Northern Ireland, and ii) in general animal welfare and food safety policy areas. As part of a larger study called PIGWELFIND, the analysis sought to explore the potential development of pig meat inspection as an animal welfare and diagnostic tool. Findings The final SWOT framework comprised two strengths, three opportunities, six weaknesses, and five threats. Issues around relationships and communication between producers and their veterinary practitioner, processors and producers were common to both the strengths and weakness clusters. Practical challenges within the processing plant were also named. Overall, the SWOT framework complements results reported in Devitt et al. (Ir Vet J 69:2, 2016) regarding problematic issues within the current system of information feedback on meat inspection especially within the Republic of Ireland, and the wider challenges of communication and problems of distrust. Conclusion The results of the SWOT analysis support the conclusions from Devitt et al. (Ir Vet J 69:2, 2016), that trust between all stakeholders across the supply chain will be essential for the development of an effective environment in which to realise the full diagnostic potential of MI data. Further stakeholder engagement could seek to apply the findings of the SWOT analysis to a policy Delphi methodology, as used elsewhere.